EFEKTIVITAS PEMBELAJARAN DARING MENGGUNAKAN MOODLE PADA MATA PELAJARAN MATEMATIKA SELAMA MASA PANDEMI COVID-19 DI SMP - supriyadi, edi; Sugiarni, Rani (Papanda Publisher, 2022)
The Covid-19 pandemic has affected almost all aspects of human life. To break the chain of transmission of the virus, many restrictions have been put in place by the government, including the Indonesian government. The use of multimedia and internet technology can change the style in transferring knowledge which is an alternative to learning in conventional classes. The purpose of this study is to provide an overview of the implementation of Learning from Home at the Junior High School Education Level during the Corona Virus Disease 19 (Covid-19) Pandemic. Based on data processing and analysis of student responses, online learning carried out by teachers in online mathematics learning using Moodle was carried out well with positive student responses in the implementation of online learning, material understanding and effectiveness in the application of online learning using Moodle.